2022
DOI: 10.3389/fmicb.2022.1059431
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigations of diarrhea in children in Praia city, Cape Verde

Abstract: IntroductionDiarrheal disease is a major cause of infant mortality and morbidity in Africa and results primarily from contaminated food and water sources, but its prevalence predictors in Cape Verde are not completely known. For this reason, this study aimed to identify the etiological agents of diarrhea in Cape Verdean children and assess its associated risk factors.MethodsA survey questionnaire was used, and a total of 105 stool samples from children with diarrhea aged 0–12 years at the Central Hospital of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
1
1
Order By: Relevance
“…In contrast to this study, a higher or non-zero prevalence of SaV was reported (19,30). The source of this variation might be either the lower prevalence of the virus during the study period in the region, reduced viral load or the predominance of other viral, bacterial and parasitic associated gastroenteritis as seen elsewhere (52,53).…”
Section: Discussioncontrasting
confidence: 82%
“…In contrast to this study, a higher or non-zero prevalence of SaV was reported (19,30). The source of this variation might be either the lower prevalence of the virus during the study period in the region, reduced viral load or the predominance of other viral, bacterial and parasitic associated gastroenteritis as seen elsewhere (52,53).…”
Section: Discussioncontrasting
confidence: 82%
“…Overall, the details of identification were consistent with the previous study reported by others. [16,17] Moreover, all diagnoses should be confirmed by the clinician. If there is any inconsistency between clinical manifestation and laboratory results, another test in a third-party laboratory should be performed to verify this result.…”
Section: Research Parametersmentioning
confidence: 99%